Shared workplace experiences of lesbian and gay police officers in the United Kingdom. Issue 2 (18th May 2015) - Colvin, Roddrick
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to explores the contemporary workplace experiences of lesbian and gay officers who serve across the UK. Design/methodology/approach – Using an online survey, the research asked lesbian and gay officers to share their experiences in law enforcement environments. Acknowledging the changing climate in many law enforcement environments, this respondents here were asked to focus on both positive and negative experiences in the workplace. Findings – The responses of 243 police officers revealed that lesbian and gay officers face barriers to equal employment opportunities similar to those faced by women and other minorities in law enforcement, but lesbian officers appear to experience and witness lower levels of discrimination than gay male police officers. Attitudinal bias against lesbian and gay officers remains a significant problem in the force. Lesbian officers report feelings of tokenism at higher levels than gay male police officers. Research limitations/implications – Future research endeavors should analyze any differences between the experiences of different lesbians and gay men at different levels of visibility within law enforcement, including "out" and "closeted" officers. Research about when officers come out as lesbian or gay – during training, on the force, after they retire – would be insightful in understanding officers' perceptions. Practical implications – The research suggests that police departments in the UK have made good strides in opening the law enforcement workforce, but continue to face on-going challenges in creating fair, diverse, and representative work environments for lesbian and gay officers. Specifically, agencies should review policies where supervisor have discretion over the employment-related actions. By not meetings the challenges of a more diverse workplace, agencies risk lower job satisfaction, and decreased police effectiveness, especially on community policing environments. Originality/value – This research joins a small, but growing body of research that offers specific barriers and opportunities – as perceived by the officers. As other agencies engage in efforts to recruit and retain diversity police forces, the results of this research can enhance policies and practices, with regards to lesbian and gay officers.